UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINKPAIR SHARE PADA TEMA PRAJA MUDA KARANADI KELAS III SD SWASTA ADVENT TIMBANG DELI - Mia Emlisa Sembiring; Ester Julinda Simarmata; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The results of this study indicated an increase in students’ learning outcomes. It was found that the average score in the pre-test was 52.66%, and the level of classical completeness was 23.3%. Then, the score in the first cycle increased after using the Think Pair Share Typed Cooperative learning model with an average score of 71.16 and a classical completeness level of 43.3%. Moreover, after conducting the post-test in cycle II, 22 students reached the minimum target of their study results, and 8 students did not. The average score of the post-test in cycle II increased to 81.33, and the classical completeness level reached 73.33%. The results obtained concluded that the Think Pair Share Typed Cooperative model improved students’ learning outcomes at grade III of SD Swasta Advent Timbang Deli in the academic year of 2020/2021. Based on the study results, teachers were suggested to use the Think Pair ShareTyped Cooperative model because it was proven to improve students’ learning outcomes.